A REVIEW OF GASTRIC ULCER FOLLOW-UP PRACTICES IN A TERTIARY CARE GASTROENTEROLOGY SERVICE. (8th June 2013) - McGlacken-Byrne, S; Lahiff, C; MacMathuna, P; Leyden, J
Abstract : Introduction: The Joint Advisory Group (JAG) guidelines1 recommend follow-up gastroscopy within 12 weeks for patients with gastric ulcers at index gastroscopy. Aims/Background: This study reviews current practice in relation to gastric ulcer follow-up at a tertiary care university hospital. Method: We conducted a retrospective review of over 700 gastroscopies performed in a four month period from June to September 2012. Patients with newly diagnosed ulcers (n=29) were included in our primary analysis. Those undergoing follow-up endoscopy for previously identified gastric ulcers (n=8) were also included. Results: Gastric ulcers were found in 29 patients during the study period. Twenty three (79%) patients had biopsies taken. A plan for follow up gastroscopy was stated in 14 (48%) reports. Of these, 12 patients (86%) had follow up procedures booked and 9 (64%) attended for repeat gastroscopies. Median time to follow-up in this group was 61 days (range 3–194) and all patients had either healed (n=3) or healing (n=6) ulcers at follow up. Of patients undergoing gastroscopy for ulcers diagnosed prior to the study period (n=8), persistent mucosal abnormalities were noted in 7 (88%) of patients. Of these, 4 patients (50%) had biopsies taken. Two of these patients (25%) had a third gastroscopy booked for follow-up. Conclusion: The data suggests that follow-up practices for gastric ulcers are not currently meeting standards set out by JAG guidelines. The performance of follow-up gastroscopy earlier than the recommended interval may result in higher prevalence of persistent mucosal abnormalities, with increased resource use accruing in terms of biopsies taken and further endoscopy.